A High-Sensitivity Refractive Index Nano-Sensor Structure Based on MIM Waveguide. Issue 1 (1st February 2023) - Liu, Pengwei; Yan, Shubin; Shen, Lifang; Liu, Jilai; Ren, Yifeng
Abstract: In this review, we engineer a high-performing nanosensor mechanic based on SPPs, which consists of a metal-insulator-metal waveguide coupled with two triangular plates in a double-internal-pile ring cavity (DISRC). The feasibility of establishing the sensor based on SPPs is analyzed theoretically, and the parameters of DISRC are simulated by the finite element method. The best sensitivity of the proposed system is 2640 nm/RIU with a high FOM is 71.4. The sensor is simple in structure, easy to integrate, and takes some advantages of traditional cavities into account. Hence, in other high-sensitivity nano-sensor fields, it has good application prospect and potential.